PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN KETERAMPILANPREPARE DANTABLE SET UP DALAM MATA KULIAH TATA HIDANG - Wahyuningsih, Wahyuningsih (Universitas Negeri Semarang, 2011)
This learning teching research was intended to improve the learning outcomes of the students practicing in the subject of prepare and table set up, the main subject of Tata Hidang I (Servicing Arragements I). The subject for this research consisted of 18 S1 students of the learning group number 02 for the study Program for PKK, concentrating on Tata Boga, Departement of Service & Production Technology, the Technical Faculty of Semarang State University for the academic period of 2009-2010. This research was conducted in the gasal semester of the academic year of 2009-2010. The needed data were collected by means of tests and obsevation on the learning outcomes of the students practicing in the sub-subject of Prepare and Table Set up. The data collection used grading sheets for practices in Tata Hidang as its instrument. The data were then analized using the method of descriptive presentation. This was a classroom-action research planned in three cycles. The second and third cycles were implemented based on reflections on the first cycle and on improvements that should be reached. Every cycle consisted of two face to face encounters and of 4 activities: (1)planning, (2) implementations, (3) observations, (4) reflections. The results of this research showed that the use of peeer tutorials for the learning-teching pocesses had positive effects both on the students and the lecturers that it might improve the quality of lecturing for the Tata Hidang I. The grades obtained by the students from practicing in the sub-subject of prepare and table set up increased from the lowest grade C (46.7%) BC and B (60%) and AB (26.6 %), and AB (26.6%.). Trough the three cycles, the number of BC grade decreased from 66% to only 20%. Based on the results of this research, it is recommended that peer tutorial for the subject of Tata Hidang I and Servicing in Food & Beverage should be continued in order that the educational serveices provided to the practicing students might be optimized and the student achievements might be improved.